Shifting perspectives on coastal impacts and adaptation - Brown, Sally (2018)
The Intergovernmental Panel on Climate Change reports reflect evolving attitudes in adapting to sea-level rise by taking a systems approach and recognizing that multiple responses exist to achieve a less hazardous coast.